Effects of habitat types, vegetation structure and proximity to forest on farm land bird species richness and abundance - Ahmui, Lijan John (2019)
Conversion of tropical forest for agricultural purposes is generally assumed to seriously threaten the survival of avian species and their habitats. Impoverished habitat quality in the matrix might influence the species composition within the agriculture areas through biotic homogenization. The aim of this study was to investigate the effects of habitat types, vegetation structure and proximity to forest on bird species richness and abundance in human-modified landscapes. Mist-nets were used to sample bird. A total of of 180 individual birds of 37 bird species representing 22 family were captured in three habitats. The highest bird species richness was found in fruit orchard followed by oil palm and rubber plantations. Avian species richness and abundance was significantly influenced by canopy cover, tree density, proximity to forest, habitat type and month. The number of tree, habitat type and month were also important predictor for total bird body weight. The findings suggested that protection of remnant forests should be prioritized to conserve bird diversity. Appropriate landscape design and habitat management could improve functional diversity in agricultural landscapes in the tropics.